Kualitas Mikrobiologis Daging Paha Ayam Broiler Direndam dalam Cairan Fermentasi Kubis (Brassica oleracea) Selama Penyimpanan Suhu Dingin (±4 0C): Microbiological Quality of Broiler Chicken Thigh Meat Soaked in Cabbage (Brassica oleracea) Fermented Liquid During Cold Storage (±4oC) - Afriani, Afriani; Illahi , Selvia Rizki Wahyu; Filawati, Filawati (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2025)
Background: Broiler chicken meat contains high nutritional content, so it is easily damaged due to contamination by microorganisms if it is not handled and stored correctly. Purpose: The aim of this research was to determine the effect of storage at cold temperatures (±4 0C) on the microbiological quality of broiler chicken thigh meat soaked in fermented cabbage (Brassica oleracea) liquid. Methods: The experimental design used was a Completely Randomized Design (CRD) with five treatments and four replications. The treatment was cold temperature storage (±4 0C) on broiler chicken thigh meat that had been soaked in fermentation liquid, namely: without cold temperature storage (P0), storage for 2 days (P1), storage for 4 days (P2), storage for 6 days (P3), and storage for 8 days (P4). The data obtained were analyzed using analysis of variance (ANOVA), and if the results were significantly different, they were further analyzed using Duncan's Multiple Range Test (DMRT). Results: The results of the analysis of variance showed that storage at cold temperatures (±4 0C) of broiler chicken thigh meat that had been soaked in fermented cabbage (Brassica oleracea) liquid had no significant effect (P>0.05) on total microbes, total BAL, and total Escherichia coli. Conclusion: Storage at cold temperatures (±4 0C) of broiler chicken thigh meat soaked in cabbage fermentation liquid for up to 8 days can maintain Total Microbes, Total Lactic Acid Bacteria (LAB), and total Escherichia coli. Total Microbes meet the Indonesian National Standard (INS), but the total E. coli has exceeded the Indonesian National Standard (INS) limit.